METTL3 suppresses pyroptosis in obstructive sleep apnea-associated hypertension via YTHDF2-mediated SOX4 mRNA degradation - Wenjun Zhu; Yanyan Hou; Can Yang; Yaping Tian; Linna Cao; Wenjun Li; Liang Xie; Lirong He (Journal of Physiology and Biochemistry, 2026)

Co-exposure of sequential extreme weather and non-biodegradable/biodegradable microplastics (NBMPs/BMPs) on soil bacterial communities and the extracellular polymeric substances (EPS)-extracellular enzyme interaction mechanisms - Xinyu Yang; Yulian Ma; Xin Wang; Yue Sun; Qianzhi Zeng; Yunhong Pu; Bowen Yang; Yaxuan Wu; Xinran Su; Linna Shi; Shuang Li; Wenzhuo Sui; et al. (Journal of Environmental Chemical Engineering, 2026)

Inhibiting Ru over-oxidation in RuO2 via vanadium doping for efficient oxygen evolution reaction toward acid and alkaline water electrolysis - Wenzhuo Zhang; Linna Wang; Xiang Li; Yunling Ji; Guisheng Xu; Yikang Cao; Shufen Wang; Jian Li (Fuel, 2026)

A novel perspective on the aging of raw Pu-erh tea: a comprehensive evaluation of the impact of different storage containers on flavor quality - Di Tian; Ting Wu; Linna Ma; Xiaohui Zhou; Chenyang Ma; Ning Chen; Haiyan Yi; Yapeng Liu; Yali Li; Yong-Quan Xu; Hongjie Zhou; Xiujuan Deng (Food Research International, 2026)

Phenothiazine-based self-assembled monolayer enabling high-efficiency and scalable inverted perovskite solar cells - Huilin Xie; Mingxin Wang; Xiaofeng He; Peng Wang; Miaoxin Li; Cheng Zhong; Qunliang Song; Yong Hua; Fei Wu; Linna Zhu (Chemical Engineering Journal, 2026)

Sulfobutylether-(hydroxypropyl-β-cyclodextrin) bonded silica as stationary phase for enhancing chiral separation in liquid chromatography - Linna Xu; Ankang Li; Jialong Wang; Gaosheng Yang; Liqin Lin; Keer Yu; Huizhen Ni; Wentao Xu; Junchao Zhu; Dongping Cheng; Shengqiang Tong (Analytica Chimica Acta, 2026)

Nonlinear and spatially heterogeneous carbon effects of three-dimensional urban expansion in China - Zilin Deng; Ziyan Luo; Linna Li; Yueting Ma; Yaqun Liu (Environmental Impact Assessment Review, 2026)

DOM-mediated interaction of DOM-enzyme-pollutants affected the toxicity of combined aged tire wear particles (aged-TWPs) and polyfluoroalkyl substances (PFASs) in soil under successive extreme weather stress - Xin Wang; Yulian Ma; Xinyu Yang; Yue Sun; Wenzhuo Sui; Yunhong Pu; Qianzhi Zeng; Yaxuan Wu; Bowen Yang; Xinran Su; Shuang Li; Linna Shi; et al. (Journal of Environmental Management, 2026)

Au/MXene hydrogel with NIR photothermal regulation promotes diabetic wound healing through synergistic induction of reactive oxygen species storms and EGCG release - Yumei Li; Xingjun Zhao; Linna Chang; Yanan Hu; Shibo Xu; Xiuli Ren; Xifan Mei; Zhenhua Chen (Chemical Engineering Journal, 2026)

Effects of Perfluoroheptanoic Acid (PFHpA) on Bacterial Community, Elemental Cycling and ARGs Transmission in Sediment - Shengnan Shi; Xinran Su; Linna Shi; Shuang Li; Yunhong Pu; Qianzhi Zeng; Bowen Yang; Yaxuan Wu; Yue Sun; Yulian Ma; Xinyu Yang; Xin Wang; et al. (Water, Air, & Soil Pollution, 2026)

Context-dependent reshaping of rhizosphere microbial communities by intercropping systems: A systematic analysis of 32 crop combinations - Feixue Li; Linna Ma; Jingyu Li; Chen Ye; Xinyue Mei; Siji Zhao; Yiwen Li; Yixiang Liu; Huichuan Huang; Xiang Li (Rhizosphere, 2026)

Enrichment mechanisms of rare earth elements associated with bauxite in northern Guizhou, China: An integrated study using microanalysis and machine learning - Shuhang Chen; Yong Fu; Feng Tian; Chuan Guo; Xinnian Li; Shuaichao Wei; Guodong Liu; Linna Wu (Journal of Asian Earth Sciences, 2026)

Explainable machine learning-assisted near-infrared spectroscopy for rapid detection of adulterants in sweet potato starch - Mengmeng Li; Linna Guo; Mengyu Zhang; Yujie Wang (Food Control, 2026)

Multifunctional extreme-temperature-tolerant photonic electronic skin for synergistic electrical and optical sensing - Jun-Tao Liu; Linna Huang; Zimo Zhang; Shulin Qin; Jia-Li Xu; Yufan Zhang; Chen Yang; Yu Tian (Chemical Engineering Journal, 2026)

Niaodukang for the treatment of chronic kidney disease: Regulation of the TRAF3/NF-κB2 signaling pathway and its improvement of the intestinal barrier - Juan Xu; Lei Wang; Hong Wang; Jie Pang; Linna Liu; Ting Zhang; Ling Yuan; Xiaoxue Cui; Qian Jiang; Yanlin Li (Tissue and Cell, 2026)

Flexural performance of CFRP grid-reinforced ultra-high performance concrete (UHPC) plates under cyclic incremental loading - JinJing Liao; Haotian Li; Yu Zheng; Linna Geng; Yan Zhuge; Jun-Jie Zeng (Engineering Structures, 2026)

Insights into low temperature adaptation in Epinephelus awoara through integrated genome and transcriptome analysis - Linna Wang; Shuai Chen; Zhentong Li; Yang Liu; Shihao Wang; Tangtang Ding; Fengfan Yang; Chunbai Zhang; Linlin Li; Wensheng Li; Qingbin Wang; Xia Zhao; et al. (Aquaculture, 2026)

Measuring forced car ownership through the lens of spatial inequality: A multi-level analysis in China - Linna Li; Zilin Deng; Jialin Jiang; Tianyang Zhang (Journal of Transport Geography, 2026)

How do digital technologies reduce carbon emissions in the construction industry? a systematic review - Linna Geng; Shengping Li; Ehsan Noroozinejad Farsangi; Xiaoxiao Xu; Vivian W.Y. Tam (Energy and Buildings, 2026)

Hydrogen peroxide–sodium carbonate pretreatment improves lignocellulose deconstruction and enzymatic saccharification of corn stover - Zejin Li; Zuhua Zhao; Lu Zhang; Linna Suo (Biomass and Bioenergy, 2026)

Petrogenesis of the Niancaowan mafic-ultramafic intrusion: Decoding magmatic evolution in the cu Ni Metallogenic Province of the Bayan obo rift zone - Linna LI; Jiangang JIAO; Yunfei MA (Geochemistry, 2025)

Influence of Economic Growth on Expansion of Urban Construction Land in the Yellow River Basin of China and Its Policy Implications - Linna Li; Wenfeng Chen; Yansui Liu (Chinese Geographical Science, 2025)

Detecting the contribution of transport development to urban construction land expansion in the Beijing-Tianjin-Hebei region of China based on machine learning - Linna Li; Chunchun Huang; Yansui Liu (Land Use Policy, 2025)

Exploring the effects of food by-product HMF on pepsin structure, function, and physiological activity from a binding perspective - Shuyuan Zhang; Zimeng He; Linna Gao; Ziye Zhou; Yiming Wang; Xiting Li; Yongye Zheng; Baozhu Chi; Xun Tuo (Food Research International, 2025)

Characterization of volatile flavour compounds and characteristic flavour precursors in poultry eggs based on multi-omics and machine learning - Hongqiang Li; Xiangmin Zhao; Xiaoming Li; Jing Liang; Shizhen Qin; Jinlu Li; Aiwen Zhang; Linna Xu; Defu Tang; Fuwei Li (Food Chemistry, 2025)

Embryonic and Larval Development of an Interspecific Grouper Backcross Between the Kelp Grouper (Epinephelus moara) ♀ and KGGG (E. moara ♀ × E. lanceolatus ♂) ♂ - Yidan Xu; Yongsheng Tian; Shihao Wang; Tangtang Ding; Linna Wang; Zhentong Li; Linlin Li; Yang Liu (Fishes, 2025)
Backcrossing serves as an effective tool for interspecific gene introgression, facilitating germplasm improvement. To develop superior grouper aquaculture varieties, in this study, a backcrossed breed was constructed by crossing a male hybrid grouper, KGGG (Epinephelus moara ♀ × E. lanceolatus ♂), with a female parent kelp grouper (KG; E. moara). Here, we observed embryonic, larval development, and morphological changes in KG × KGGG. Additionally, the total length and body weight of the backcrossed breed and maternal parent were compared at 160 d post hatching (dph). The results showed that fertilization and the hatching rate were 73.23 ± 4.23% and 51.74 ± 3.67%, respectively, and the egg size was 0.89 ± 0.03 mm. Hatching occurred 23:19 h after fertilization at 25 ± 1 °C, and the newly hatched larvae were 1.94 ± 0.13 mm in length. Furthermore, at 160 dph, the total length and body weight of the backcrossed breed were 1.2-fold and 1.9-fold greater, respectively, when compared with those of the maternal parent. Importantly, it is possible that backcrossed KG × KGGG could become a dominant strain in grouper aquaculture practices.

Synergistic bioaugmentation: Serratia sp. WKD and carboxymethyl cellulose-modified nano-zero-valent iron enhance malachite green decolorization by activated sludge - Linna Du; Xinjiao Dong; Huan Wu; Gang Li; Jiacheng Zhou; Yiqing Wu; Yanping Xiao; Jing Qin; Xiu Wang (Journal of Water Process Engineering, 2025)

Compartment-specific core microbiomes and functions in rice - Linna Ma; Yusha Bai; Xiang Li; Jingyu Li; Feixue Li; Yan Yue; Yingguang Li; Jingwen Guo; Chen Ye; Xinyue Mei; Fei Du; Yixiang Liu; et al. (Plant and Soil, 2025)

UGPase: A novel molecule that regulates LPS synthesis, virulence, and immunogenicity of Brucella melitensis - Si Chen; Yuxin Liu; Yang Gao; Dong Zhang; Ru Zhang; Fei Tu; Nan Li; Qingkui Jiang; Linna Liu; Yanling Yang (Veterinary Microbiology, 2025)

Structural and functional alterations of human serum albumin (HSA) induced by TBBPS-BME: A spectroscopic, computational, and molecular dynamics study - Wei Zhang; Linna Gao; Shuyuan Zhang; Jiaqing Luo; Ruoxuan Yu; Xiting Li; Zhili Lu; Baozhu Chi; Ying Guo; Xun Tuo (Chemico-Biological Interactions, 2025)

Soil microbial community and chemical properties response to blueberry–soybean intercropping system - Linna Ma; Xiang Li; Zhiping Zhang; Ting Zhang; Haibin Duan; Huichuan Huang; Yixiang Liu; Shusheng Zhu; Youyong Zhu; Yingbin Li (Plant and Soil, 2025)

Dynamic simulation of core power control for SPWR based on dynamic model bank - Zheng Li; Xiaoyu Li; Linna Wang; Wenjie Zeng (Annals of Nuclear Energy, 2025)

Bacillus velezensis SS-20 as a potential and efficient multifunctional agent in biocontrol, saline-alkaline tolerance, and plant-growth promotion - Zhaoliang Chen; Haiyun Zhang; Weiguang Lv; Siyi Zhang; Linna Du; Shuangxi Li; Hanlin Zhang; Xianqing Zheng; Juanqin Zhang; Tinglin Zhang; Naling Bai (Applied Soil Ecology, 2025)

Toward crop–livestock integration: a comprehensive framework for cropping system adaptation assessment to mitigate forage shortage - Dan Liu; Jianjun Jin; Xin Qiu; Rui He; Linna Li; Jie Yang (Environment, Development and Sustainability, 2024)

Corrigendum to ‘Heavy metals and metalloids exposure and liver function in Chinese adults - A nationally representative cross-sectional study’ [Environ. Res. 252-P2 (2024) 118653] - Shiyu Wang; Yuebin Lyu; Saisai Ji; Nankun Liu; Bing Wu; Feng Zhao; Zheng Li; Yingli Qu; Yuanduo Zhu; Linna Xie; Yawei Li; Zheng Zhang; et al. (Environmental Research, 2024)

TaSRT2 recognizes a viral protein to activate host immunity by increasing histone acetylation - Kaili Zhong; Yaoyao Jiang; Haichao Hu; Bowen Yuan; Mila Wu; Aizhu Tu; Gecheng Xu; Linna Cai; Tingting Liu; Shiqi Gao; Linzhi Li; Qiansheng Liao; et al. (Science Bulletin, 2024)

Impact of corticosteroid doses on prognosis of severe and critical COVID-19 patients with Omicron variant infection: a propensity score matching study - Shiyao Wang; Ziying Chen; Xinran Zhang; Xiaojing Wu; Yuqiong Wang; Qi Zhang; Linna Huang; Xiaoyang Cui; Ying Cai; Xu Huang; Jingen Xia; Sichao Gu; et al. (Inflammopharmacology, 2024)
Background There is lack of research on corticosteroid use for severe and critical COVID-19 patients with Omicron variant infection. Methods This multi-center retrospective cohort study involved 1167 patients from 59 ICUs across the mainland of China diagnosed with severe or critical SARS-CoV-2 Omicron variant infection between November 1, 2022, and February 11, 2023. Patients were segregated into two groups based on their corticosteroid treatment—usual dose (equivalent prednisone dose 30–50 mg/day) and higher dose (equivalent prednisone dose > 50 mg/day). The primary outcome was 28-day ICU mortality. Propensity score matching was used to compare outcomes between cohorts. Results After propensity score matching, 520 patients in the usual dose corticosteroid group and 260 patients in the higher dose corticosteroid group were included in the analysis, respectively. The mortality was significantly higher in the higher dose corticosteroid group (67.3%, 175/260) compared to the usual dose group (56.0%, 291/520). Logistic regression showed that higher doses of corticosteroids were significantly associated with increased mortality at 28-day (OR = 1.62,95% CI 1.19–2.21, p = 0.002) and mortality in ICU stay (OR = 1.66,95% CI 1.21–2.28, p = 0.002). Different types of corticosteroids did not affect the effect. Conclusions The study suggests that higher-dose corticosteroids may lead to a poorer prognosis for severe and critical COVID-19 patients with Omicron variant infection in the ICU. Further research is needed to determine the appropriate corticosteroid dosage for these patients.

The gut microbiome: an important role in neurodegenerative diseases and their therapeutic advances - Songlin Li; Linna Zhao; Jie Xiao; Yuying Guo; Rong Fu; Yunsha Zhang; Shixin Xu (Molecular and Cellular Biochemistry, 2024)

Steep oceanic DIC δ13C depth gradient during the Hirnantian Glaciation - Shengchao Yang; Junxuan Fan; Thomas J. Algeo; Graham A. Shields; Ying Zhou; Chao Li; Jitao Chen; Weiqiang Li; Na Li; Jian Cao; Linna Zhang; Zongyuan Sun; et al. (Earth-Science Reviews, 2024)

Nonlinear relationship between urban form and transport CO2 emissions: Evidence from Chinese cities based on machine learning - Linna Li; Zilin Deng; Xiaoyan Huang (Journal of Geographical Sciences, 2024)

Bionic nanopore recognition receptors for single-molecule enantioselectivity studies of chiral drugs - Rikun Cui; Zhenzhao Wang; Linna Li; Lili Liu; Zhen Li; Xingtong Liu; Tingting Chen; Ayesha Rauf; Xiaofeng Kang; Yanli Guo (Analytica Chimica Acta, 2024)

Dietary seafood as a potential modifier in the relationship between per- and polyfluoroalkyl substances (PFASs) burden and prediabetes/diabetes: Insights from a nationally representative cross-sectional study - Yingli Qu; Nan Sheng; Saisai Ji; Zheng Li; Jinghua Wang; Yitao Pan; Xiaojian Hu; Xulin Zheng; Yawei Li; Haocan Song; Linna Xie; Wenli Zhang; et al. (Journal of Hazardous Materials, 2024)

Heavy metals and metalloids exposure and liver function in Chinese adults — A nationally representative cross-sectional study - Shiyu Wang; Yuebin Lyu; Saisai Ji; Nankun Liu; Bing Wu; Feng Zhao; Zheng Li; Yingli Qu; Yuanduo Zhu; Linna Xie; Yawei Li; Zheng Zhang; et al. (Environmental Research, 2024)

Spatio-temporal evolution and topographic gradient effect of land use and ecosystem service value in the Lhasa River Basin - Jianwei Zhou; Bin Feng; Hua Wu; Tong Xu; Linna Chen; Xinyong Zhao; Qiyun Guo; Jiatong Li; Chenguang Zhang; Kangcheng Zhu; Yuzhong Kong (Journal of Mountain Science, 2024)

Paleontology Knowledge Graph for Data-Driven Discovery - Yiying Deng; Sicun Song; Junxuan Fan; Mao Luo; Le Yao; Shaochun Dong; Yukun Shi; Linna Zhang; Yue Wang; Haipeng Xu; Huiqing Xu; Yingying Zhao; et al. (Journal of Earth Science, 2024)

Simultaneously enhancing sensitivity and operation range of flexible pressure sensor by constructing a magnetic-guided microstructure in laser-induced graphene composite - Linna Mao; Taisong Pan; Lin Lin; Yizhen Ke; Hengjie Su; Yue Li; Wen Huang; Ting Li; Yuan Lin (Chemical Engineering Journal, 2024)

Comparative transcriptome analysis of hybrid Jinhu grouper (Epinephelus fuscoguttatus ♀ × Epinephelus tukula ♂) and Epinephelus fuscoguttatus under temperature stress - Pengfei Duan; Yongsheng Tian; Zhentong Li; Shuai Chen; Linlin Li; Xinyi Wang; Linna Wang; Yang Liu; Jieming Zhai; Wensheng Li; Qingbin Wang; Wenhui Ma; et al. (Aquaculture, 2024)

How does transport development contribute to rural income in China? Evidence from county-level analysis using structural equation model - Linna Li; Jiayuan Cai; Wenfeng Chen (Travel Behaviour and Society, 2024)

Performance comparison of anthocyanin-based smart indicator films - Zhigang Xiao; Linna Han; Mengqing Gu; Yiqun Zhu; Yifan Zhang; Zhe Li; Tiemin Xie; Fei Lu (Food Packaging and Shelf Life, 2023)

Preparation of hypercrosslinked porous polymer with manifold functional groups for sensitive determination of phenylurea herbicides in beverages and celtuce samples - Linna Guo; Miao Tian; Zhi Li; Qianqian Wang; Qiuhua Wu; Lin Hao; Chun Wang (Food Chemistry, 2023)

Copper/gold-modified porphyrinic metal–organic frameworks nanoprobes for enhanced photodynamic/chemodynamic therapy - Jiahe Zhang; Linna Chang; Ran Hao; Gangwan Zhang; Tao Liu; Zekai Li; Tianyou Wang; Leyong Zeng (Chemical Engineering Journal, 2023)

Reducing road transport emissions for climate policy in China and India - Becky P.Y. Loo; Linna Li; Anil Namdeo (Transportation Research Part D: Transport and Environment, 2023)

Effect of sunflower seed husk and rape straw in total mixed ration during peri-puberty on testis development in Hu lambs - Xiuxiu Weng; Wanhong Li; Hui Xu; Shirong Li; Xinji Wang; Kaidong Li; Linna Xu; Jiamei Liu; Xiangpeng Yue; Fadi Li (Small Ruminant Research, 2023)

Effect of non-permeable cryoprotectant sucrose on the development of spotted knifejaw (Oplegnathus punctatus) embryos - Linlin Li; Yongsheng Tian; Zhentong Li; Pengfei Duan; Xinyi Wang; Shuai Chen; Linna Wang; Yang Liu; Qingbin Wang; Wensheng Li; Xia Zhao; Wenhui Ma; et al. (Cryobiology, 2023)

Schiff base reaction induced densification of chitosan-derived microporous carbon for compact capacitive energy storage - Jun Zhang; Tingting Tang; Xuemeng Gan; Renlu Yuan; Qiqi Li; Linna Zhu; Nannan Guo; Jiayao Zhu; Yutong Li; Su Zhang; Zhuangjun Fan; Huaihe Song (Chemical Engineering Journal, 2023)

Catalytic probes based on aggregation-induced emission-active Au nanoclusters for visualizing MicroRNA in living cells and in vivo - Wenhao Shu; Xuetao Zhang; Hongmei Tang; Linna Wang; Manxiao Cheng; Jingwen Xu; Rong Li; Xiang Ran (Analytica Chimica Acta, 2023)

Identification of a phosphotriesterase-like lactonase in Klebsiella sp. and enhancement of its biofouling mitigation potential by γ-caprolactone - Xinjiao Dong; Dong Liu; Linna Du; Shimei Ge; Yizhu Zhao; Yaru Li; Chuanhua Wang (International Biodeterioration & Biodegradation, 2023)

Efficient degradation and decolorization of triphenylmethane dyes by Serratia sp. WKD under extreme environmental conditions and the mechanism - Linna Du; Huan Wu; Gang Li; Yi Wei; Fei Wang; Ligen Xu; Xinjiao Dong (International Biodeterioration & Biodegradation, 2023)

Evaluating the human use efficiency of urban built environment and their coordinated development in a spatially refined manner - Yi Bao; Zhou Huang; Linna Li; Han Wang; Jiayuan Lin; Gang Liu (Resources, Conservation and Recycling, 2023)

Stem Cell-derived Extracellular Vesicles: A Promising Nano Delivery Platform to the Brain? - Yuying Guo; Dongsheng Hu; Lu Lian; Linna Zhao; Mingli Li; Huijing Bao; Shixin Xu (Stem Cell Reviews and Reports, 2023)

Heterosis in growth and low temperature tolerance in Jinhu grouper (Epinephelus fuscoguttatus ♀ × Epinephelus tukula ♂) - Shuai Chen; Yongsheng Tian; Zhentong Li; Yang Liu; Ziqi Li; Pengfei Duan; Linlin Li; Xinyi Wang; Linna Wang; Xinlei He; Xia Zhao; Wensheng Li; et al. (Aquaculture, 2023)

Decoupling analysis of China's mining industrial development and water usage: Based on production-based and consumption-based perspectives - Yiming Li; Yingnan Zhang; Lin Yang; Fenglian Du; Linna Sai; Bin Zhang (Journal of Cleaner Production, 2023)

Genome-wide analysis of CtNF-YB and lipid synthesis regulation of CtNF-YB12 in Carthamus tinctorius L. - Sinan Deng; Ruinan Wang; Chenlu Tao; Lixia Li; Shuai Wang; Chang Jia; Yilin Liu; Ruo Du; Linna Du; Jing Yang (Plant Cell Reports, 2023)

Sensitivity analysis of heat transfer coefficient in primary system for LMSR core power control system based on Sobol’s method - Lehua Liang; Chuhao Li; Linna Wang; Xuejian Wang; Wenjie Zeng; Run Luo (Annals of Nuclear Energy, 2023)

Remote Estimation of the Chlorophyll-a Concentration in Lake Dianshan, China Using High-Spatial-Resolution Satellite Imagery - Xiaoman Lu; Chunyan Situ; Jiajia Wang; Liguo Zhou; Weichun Ma; Linna Li (Journal of the Indian Society of Remote Sensing, 2022)

Heavy Precipitation over the Jing-Jin-Ji Region in Early October: What Controls Its Interannual Variability? - Jing Feng; Tim Li; Ji Wang; Linna Zhang (Journal of Meteorological Research, 2022)

The poverty evolution of typical countries along the Belt and Road and implications from China’s poverty reduction experiences - Linna Shi; Yongsheng Wang; Yansui Liu; Yuheng Li (Journal of Geographical Sciences, 2022)

Component changes of mulberry leaf tea processed with honey and its application to in vitro and in vivo models of diabetes - Huixin Bai; Wei Jiang; Xufang Wang; Na Hu; Linna Liu; Xi Li; Yanhua Xie; Siwang Wang (Food Additives & Contaminants: Part A, 2021)

The complete mitochondrial genome of the hybrid grouper Epinephelus moara (♀)×Epinephelus tukula (♂), and phylogenetic analysis in subfamily Epinephelinae - Zhentong Li; Yongsheng Tian; Meiling Cheng; Linna Wang; Jingjing Zhang; Yuping Wu; Zunfang Pang; Wenhui Ma; Jieming Zhai (Acta Oceanologica Sinica, 2020)

Exploring the urban-rural development differences and influencing factors in the Huang-Huai-Hai Plain of China - Mingyang Cheng; Linna Li; Yang Zhou (Journal of Geographical Sciences, 2020)

De novo variants in the Helicase-C domain of CHD8 are associated with severe phenotypes including autism, language disability and overgrowth - Yu An; Linna Zhang; Wenwen Liu; Yunyun Jiang; Xue Chen; Xiaoping Lan; Gan Li; Qiang Hang; Jian Wang; James F. Gusella; Yasong Du; Yiping Shen (Human Genetics, 2020)

Comparative analysis of four semi-analytical models for estimating chlorophyll- a concentration in case-2 waters using field hyperspectral reflectance - Xiaoman Lu; Chunyan Situ; Weichun Ma; Xiaoyan Dai; Cheng He; Linna Li; Liguo Zhou (International Journal of Remote Sensing, 2020)

Geochemical behaviors of antimony in mining-affected water environment (Southwest China) - Ling Li; Han Tu; Shui Zhang; Linna Wu; Min Wu; Yang Tang; Pan Wu (Environmental Geochemistry and Health, 2019)

Efficient isolation of protoplasts from freesia callus and its application in transient expression assays - Xiaotong Shan; Yueqing Li; Liudi Zhou; Linna Tong; Chao Wei; Lijun Qiu; Xiang Gao; Li Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Effects of mining activities on evolution of water chemistry in coal-bearing aquifers in karst region of Midwestern Guizhou, China: evidences from δ13C of dissolved inorganic carbon and δ34S of sulfate - Qingguang Li; Pan Wu; Xuefang Zha; Xuexian Li; Linna Wu; Shangyi Gu (Environmental Science and Pollution Research, 2018)

Cloning, Expression, and Biochemical Characterization of Two New Oligoalginate Lyases with Synergistic Degradation Capability - Shangyong Li; Linna Wang; Xuehong Chen; Wenwen Zhao; Mi Sun; Yantao Han (Marine Biotechnology, 2018)

Optimization of wind-marine hybrid power system configuration based on genetic algorithm - Hongda Shi; Linna Li; Chenyu Zhao (Journal of Ocean University of China, 2017)

Potential deformation and its application to the diagnosis of heavy precipitation in mesoscale convective systems - Na Li; Lingkun Ran; Linna Zhang; Shouting Gao (Advances in Atmospheric Sciences, 2017)

Suitable hepatitis B vaccine for adult immunization in China - Linna Yang; Jun Yao; Jing Li; Yongdi Chen; Zheng-gang Jiang; Jing-jing Ren; Kai-jin Xu; Bing Ruan; Shi-gui Yang; Bing Wang; Tian-sheng Xie; Qian Li (Immunologic Research, 2016)

A new κ-carrageenase CgkS from marine bacterium Shewanella sp. Kz7 - Linna Wang; Shangyong Li; Shilong Zhang; Jiejing Li; Wengong Yu; Qianhong Gong (Journal of Ocean University of China, 2015)

Cloning, overexpression and characterization of a new oligoalginate lyase from a marine bacterium, Shewanella sp. - Linna Wang; Shangyong Li; Wengong Yu; Qianhong Gong (Biotechnology Letters, 2015)

One-step integration of multiple genes into the oleaginous yeast Yarrowia lipolytica - Shuliang Gao; Linna Han; Li Zhu; Mei Ge; Sheng Yang; Yu Jiang; Daijie Chen (Biotechnology Letters, 2014)

Purification and characterization of a new thermostable κ-carrageenase from the marine bacterium Pseudoalteromonas sp. QY203 - Shangyong Li; Panpan Jia; Linna Wang; Wengong Yu; Feng Han (Journal of Ocean University of China, 2013)

Progresses on microwave remote sensing of land surface parameters - JianCheng Shi; Yang Du; JinYang Du; LingMei Jiang; LinNa Chai; KeBiao Mao; Peng Xu; WenJian Ni; Chuan Xiong; Qiang Liu; ChenZhou Liu; Peng Guo; et al. (Science China Earth Sciences, 2012)

NOTCH1 regulates migration and invasion of skin cancer cells by E-cadherin repression - Zhipeng Wang; Linna Liu; Meng Wang; Min Shen; Jing Li; Juanjuan Liu; Chen Li; Chunyan Xin; Shaojun Zhu; Qibing Mei; Yukun Wang (Molecular and Cellular Biochemistry, 2012)

Private car travel characteristics and influencing factors in chinese cities —A case study of Guangzhou in Guangdong, China - Xiaoshu Cao; Hemei Chen; Linna Li; Feng Zhen (Chinese Geographical Science, 2009)

A rapid method for detection of PrP by surface plasmon resonance (SPR) - Wan Jiayu; Wang Xiong; Li Jiping; Liu Wensen; Xu Ming; Liu Linna; Xu Jing; Wang Haiying; Gao Hongwei (Archives of Virology, 2009)

Mapping of genetic modifiers of Eya1 bor/bor in CAST/EiJ and BALB/cJ that suppress cochlear aplasia and associated deafness - Haoru Niu; Xin Li; Linna Makmura; Rick A. Friedman (Mammalian Genome, 2008)